SYAIR AQAID SAEKET SEBAGAI METODE DAKWAH DALAM MENANAMKAN AQIDAH AHLUSSUNNAH WAL JAMAAH AN-NAHDLIYAH - Nadrotin Mawaddah; Dita Aulia Rahmah; Masyhuri Masyhuri (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2021)
The da’wah method of KHR. Syamsul Arifin and KHR. As'ad Syamsul Arifin in instilling aqidah Ahlussunnah Wal Jama'ah An-Nahdliyah using Syair Aqaid Saeket and how to make it exist untill now are the interesting and necessary topic for this research. With qualitative method that focuses on content analysis and empirical data, the results of the study is concluded as follows: First, Syair Aqaid saeket is a beautiful verse written by two Ulama which contains fifty aqaid, the names of the Prophets, the book of Allah, Malaikat, the pillars of Islam and the pillars of Islamic faith which is a completed-enough summary of aqidah Ahlussunnah Wal Jama'ah An-Nahdliyah. Second, the method of da'wah in this verse is da'wah bi al-qalam and bi al-lisan by using the psychological and cultural approach, namely regional language (Madura). Third, the everlastingness of this verse is supported by several factors; the method of habituation or repetition, spreading by the students, graduates, sympathizers, and several jam'iyah, and also because of the figures of the two authors.